A conformationally stressed novel ball-type perylenediimide appended zinc(II) phthalocyanine hybrid: spectroelectrochemical, electrocolorimetric and photovoltaic properties - ÖZKAYA, ALİ RIZA (ROYAL SOC CHEMISTRY, 2015)
A supramolecule, 6, based on an electron-donor zinc phthalocyanine (ZnPc) and an electron-acceptor perylene diimide (PDI) has been synthesized and characterized by elemental analysis, UV/Vis, IR, H-1 NMR and solid state C-13 CPMAS NMR and also MALDI-TOF and ICP mass spectrometry. The PDI appended ZnPc core brings about a geometrical constraint in the molecule with intriguing spectroscopic, electrochemical and photovoltaic properties. The first reduction process of 6 occurs on the PDI core while the first oxidation takes place on the Pc ring. These processes reflect a considerably small HOMO-LUMO gap of 1.50 eV, which has vital importance for optoelectronic applications. In addition, the PDI-based first and second reduction processes of 6 are accompanied by an electrochromic behaviour with colour changes from dark purple to blue and blue to turquoise, respectively. A photovoltaic cell involving 6 as the donor and [6,6]-phenyl C-61 butyric acid methyl ester as the acceptor has been fabricated. The measurements of the effect of annealing temperature on its performance indicated that the annealing process gives rise to a significant increase in the open circuit voltage, the fill factor and the photoconversion efficiency.
Keywords: SOLAR-ENERGY CONVERSION; SPECTROSCOPIC PROPERTIES; SENSING PROPERTIES; PHOTOPHYSICS; COMPLEXATION; ELECTRON; DYADS; MONO